Association of hemodynamic parameters and cardiovascular risk factors with cardiac remodeling in young patients with prehypertension and hypertension - O. N. Antropova; S. B. Silkina; I. G. Polyakova; T. V. Perevozchikova (Российский кардиологический журнал, 2020)
Aim. To assess the prevalence of left ventricular (LV) remodeling and identify its association with hemodynamic parameters and cardiovascular risk factors in young patients with prehypertension (preHTN) and hypertension (HTN).Material and methods. Group 1 (n=47) included patients with preHTN, group 2 (n=65) — patients with untreated HTN (age — 25-44 years). We performed 24-hour ambulatory blood pressure (BP) monitoring using a BpLAB monitor (OOO Petr Telegin). Echocardiography was carried out using a EnVisorC ultrasound system (Philips, Netherlands). Statistical analysis was performed using the software package Microsoft Excel 2010.Results. We revealed that 2,4% and 17,0% (p=0,002) of patients with preHTN and HTN had LV concentric remodeling, respectively; LV hypertrophy was recorded in 9,5% and 12,0% of patients, respectively. In group 1, a moderate positive relationship was found between the ratio of early to late peak velocities (E/A) and the average 24-hour aortic BP (r=0,66, p<0,05) was revealed. We also identified correlation of the augmentation index with the LV mass index (LVMI) (r=0,57, p<0,05) and LV relative wall thickness (RWT) (r=-0,7, p<0,05). In hypertensive patients, a correlation of LVMI and left atrial dimensions with a decrease in peripheral systolic blood pressure (SBP) and diastolic blood pressure (DBP) at night was found. A correlation of average 24-hour aortic BP and E/A (r=0,58, p<0,05), LV posterior wall thickness (r=0,53, p<0,05) and LV end-diastolic volume (r=0,45, p<0,05) was also revealed. A direct effect of BMI, waist circumference, uric acid values on echocardiographic data in patients with preHTN and HTN was detected.Conclusion. Despite the age, young patients with preHTN and HTN can have LV concentric remodeling and hypertrophy. LV geometry is correlated with obesity and uric acid values; in preHTN patients — with vascular stiffness and 24-hour aortic BP, in HTN patients — with 24-hour central and peripheral BP.